Serotonin enhances solitariness in phase transition of the migratory locust - Guo, Xiaojiao; Ma, Zongyuan; Kang, Le (Frontiers in Behavioral Neuroscience, 2013)
The behavioral plasticity of locusts is a striking trait presented during the reversible phase transition between solitary and gregarious individuals. However, the results of serotonin as a neurotransmitter from the migratory locust Locusta migratoria in phase transition showed an alternative profile compared to the results from the desert locust Schistoserca gregaria. In this study, we investigated the roles of serotonin in the brain during the phase change of the migratory locust. During the isolation of gregarious nymphs, the concentration of serotonin in the brain increased significantly, whereas serotonin receptors (i.e. 5-HT1, 5-HT2 and 5-HT7) we identified here showed invariable expression patterns. Pharmacological intervention showed that serotonin injection in the brain of gregarious nymphs did not induced the behavior change toward solitariness, but injection of this chemical in isolated gregarious nymphs accelerated the behavioral change from gregarious to solitary phase. During the crowding of solitary nymphs, the concentration of serotonin in the brain remained unchanged, whereas 5-HT2 increased after 1 h of crowding and maintained stable expression level thereafter. Activation of serotonin-5-HT2 signaling with a pharmaceutical agonist inhibited the gregariousness of solitary nymphs in crowding treatment. These results indicate that the fluctuations of serotonin content and 5-HT2 expression are results of locust phase change. Overall, this study demonstrates that serotonin enhances the solitariness of the gregarious locusts. Serotonin may regulate the withdrawal-like behavioral pattern displayed during locust phase change and this mechanism is conserved in different locust species.